(untitled) (Ustozlar uchun, 2024)
Abstract. In this article, not only the education system, but also an important comparative analysis of the higher education system of Finland and Uzbekistan, one of the most developed countries in the world, is covered. In addition, information is given on the main purpose of the Finnish education system and how to organize independent education for its students. At the same time, information was given about the advantages of organizing independent education using the Finnish education system in Uzbekistan's higher education institutions.